Prevalence, extent and severity of the psychosocial impact of dental aesthetics among Malaysian adolescents - Wan Nurazreena Wan Hassan; Zamros Y.M. Yusof; Sze Wan Yuen; Zawani Mohd Tajudin; Najihah Lokman; Mohd Zambri Mohamed Makhbul (Penerbit Universiti Kebangsaan Malaysia, 2019)
This study aimed to assess the prevalence, extent and severity of the psychosocial impact of dental aesthetics (PIDA) among Malaysian adolescents especially those with self-perceived malocclusion, and to determine if age and gender affected their PIDA. A cross-sectional study using a self-administered questionnaire was conducted on 12-17 year old schoolchildren from schools across Malaysia selected via a multi-stage sampling method. The questionnaire included the Malaysian Psychosocial Impact of Dental Aesthetics (Malaysian PIDA) questionnaire and the Aesthetic Component of the Index of Orthodontic Treatment Need (IOTN-AC). The Malaysian PIDA measured four domains: (Dental Self Confidence, 6 items; Social Impact, 8 items; Psychological Impact, 6 items; and Aesthetic Concern, 2 items) to assess impacts on the oral health-related quality of life specific to malocclusion. While the IOTN-AC comprised a 10-point photographic scale to assess self-perceived malocclusion. Data analysis using SPSS version 20 was involved using complete data on 901 participants. The prevalence of PIDA was 90.0% while prevalence associated with self-perceived malocclusion was 96.0%. Impact of dental aesthetics was highest on the psychological wellbeing of the adolescents, followed by their self-confidence. In terms of the extent of impact, 14.0% reported significant impact on all four domains and 19.2% were associated with self-perceived malocclusion. The prevalence of impacts was higher in younger adolescents and females. In terms of the extent and severity of impacts, younger adolescents reported higher impacts but with small effect sizes, while differences between boys and girls were not significant.